PENGARUH STRES KERJA DAN LINGKUNGAN KERJA TERHADAP TURNOVER INTENTION KARYAWAN DENGAN KEPUASAN KERJA SEBAGAI VARIABEL INTERVENING (Studi pada Karyawan PT Dankos Farma) - Cahyo Seto Pambudi; Indi Djastuti (Faculty of Economics and Business | Universitas Diponegoro, 2019)
This study was made based on the phenomenon that occurs in PT Dankos Farma that a high turnover rate encounter the company based on the data between March 2017 to March 2018. This study aims to determine and analyze the influence of job stress and working environment on employee’s turnover intention through job satisfaction as a mediator in pharmacy company in Indonesia, namely PT Dankos Farma. Job satisfaction was chosen as the mediator as it is the primary determinant of turnover intention (Mobley et al., 1979) This study uses data sources from primary data through the distribution of research questionnaires, and secondary data through journals, books, and relevant data obtained from the company. This study uses a non-probability sampling approach, more specifically the purposive sampling through the distribution of questionnaires to 119 respondents of PT Dankos Farma employees. The data analysis technique used in this study is Hierarchical Regression with IBM SPSS 23 application to find out the validity test, reliability test, classic assumption test, t test, F test, coefficient of determination test, and sobel test to find out the mediation effect. Analysis of the statistical testing result showed that job stress had significant negative effect on job satisfaction, and had significant positive effect on turnover intention. While working environment had significant positive effect on job satisfaction, and had a significant negative impact on turnover intention. Job satisfaction had a significant negative impact on turnover intention. In addition, it is also known that job satisfaction variables can mediate the indirect relationship between job stress and job satisfaction on turnover intention.